Natural Monopolies: Problems of Functioning and Reorganazation in the Context of Development of Oil and Gas Industry - Гречаник, Б. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The summary. The investigation of the functioning of the natural monopolies (fuel and energy complex) and especially as the course of the process of "deregulation" in terms of the establishment of the market (lìberalìzovanoï). You have identified the major problems that hinder the process of "deregulation" of domestic natural monopolies. Studies were carried out on the basis of the totality of the general scientific methods, namely: methods of analysis and synthesis, induction and deduction, a systemic approach isfor the study of the conceptual bases of functioning and reorganization of natural monopolies; for the analysis of the regulatory-legal support "deregulation" of domestic natural monopolies; to study the recommendations and proposals for activating processes of the liberalisation of the gas and power markets in Ukraine; method comparisons is to identify the features of the software process "deregulation" in the EU and Ukraine; statistical analysis is to evaluate the economic potential of domestic enterprises in the oil and gas industry. Offered a series of recommendations for revitalizing the process of liberalisation of the gas and power markets in Ukraine, associated primarily with the implementation of our country of the third energopaketu. Received a number of conclusions concerning the need and "extensions" of policy documents on reforming domestic energy taking into account the regional characteristics for the development of alternative energy and sustainable energy systems. Found that one of the systemic problems of national energy technical and economic nature of the problem remains "critical level" physical wear and tear of fixed assets and underestimating their value.